2001
DOI: 10.1021/bi015584b
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phototransduction in Short-Wavelength Cone Visual Pigments via the Retinylidene Schiff Base Counterion

Abstract: Short-wavelength visual pigments (SWS1) have lambda(max) values that range from the ultraviolet to the blue. Like all visual pigments, this class has an 11-cis-retinal chromophore attached through a Schiff base linkage to a lysine residue of opsin apoprotein. We have characterized a series of site-specific mutants at a conserved acidic residue in transmembrane helix 3 in the Xenopus short-wavelength sensitive cone opsin (VCOP, lambda(max) approximately 427 nm). We report the identification of D108 as the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
83
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 23 publications
8
83
0
Order By: Relevance
“…Expression constructs and COS1 cell transfections were described previously (16). MUV samples had A 357 Ϸ 0.3-0.4 with an A 280 ͞A max ratio of Ϸ4, and the E108Q mutant had A 354 Ϸ 0.3-0.4 and an A 280 ͞A max ratio of Ϸ4.5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression constructs and COS1 cell transfections were described previously (16). MUV samples had A 357 Ϸ 0.3-0.4 with an A 280 ͞A max ratio of Ϸ4, and the E108Q mutant had A 354 Ϸ 0.3-0.4 and an A 280 ͞A max ratio of Ϸ4.5.…”
Section: Methodsmentioning
confidence: 99%
“…Light-dependent activation of bovine transducin by using filter binding assays were carried out as described (16,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When T93P, L116V, and S118T are introduced into the ancestral pigment, they do not cause any significant l maxshift individually (Figure 3). Babu et al (2001) have found that the reverse mutation, D113E, in the frog pigment decreases the l max -value by 12 nm. Much to our surprise, however, when E113D is introduced into the ancestral pigment, the mutant pigment also decreases the l max by 4 nm (Figure 3), a direction that is the opposite of that predicted from the previous observation.…”
Section: Tablementioning
confidence: 99%
“…The molecular analyses of avian and mammalian pigments show that the differentiations of UV and violet pigments have occurred by the accumulations of various amino acid replacements at a total of 11 sites, 46,49,52,86,90,93,97,113,114,116, and 118 in TM helices I-III, where amino acid site numbers are standardized by those of the bovine rhodopsin (Wilkie et al 2000;Yokoyama and Shi 2000;Babu et al 2001;Shi et al 2001;Cowing et al 2002;Fasick et al 2002;Shi and Yokoyama 2003;Parry et al 2004;Yokoyama and Tada 2005;Yokoyamaet al 2005b). Furthermore, engineered ancestral pigments of a wide range of vertebrates show that most vertebrate ancestors, including the common ancestor, had UV pigments.…”
mentioning
confidence: 99%